Pathogenetic Reasoning of Administration of Mucolytic Agents for Respiratory Diseases in Children - Ye.I. Yulish (Zaslavsky O.Yu., 2015)
The paper presents the mechanisms of cough and bronchial obstruction in lesions of the respiratory tract of various origins. The effect of microbial biofilms on the course of diseases was considered particularly. The methods to restore bronchial drainage function and pathogenetic rationale for the choice of mucolytic agents were provided.